DETERMINANT INTERELATION CUSTOMER LOYALTY OF TELKOMSEL PREPAID CARD IN JAKARTA - Devi Ayuni; Andy Mulyana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
In recent decades the mobile telecommunications technology has grown very rapidly. The deregulation of the telecommunications sector opens greater opportunities for telecommunications companies to compete to provide cellular service. Competition is extremely tight lead mobile telecommunications company strategy and redesign the business to survive and improve their competitive advantage. One of the survival strategies undertaken by establishing customer loyalty. This study aims to analyze the determinants of loyalty interrelation consisting of service quality, perceived value and customer satisfaction. The population used in this study were students Sympathy GSM prepaid card users. For the purposes of quantitative analysis, determination of scores for each item questionnaire used a Likert Scale. While processing the data using SEM with LISREL 8.7 software assistance. Validity and reliability using Confirmatory Factor Analysis (CFA). From six hypothesis, 5 were accepted while others rejected 1. Quality services and significant positive effect on perceived value and customer satisfaction, but had no effect on customer loyalty. The influence of service quality on satisfaction is greater than the influence of service quality on perceived value. Service satisfaction and loyalty is influenced by perceived customer value. The influence of perceived value on loyalty greater than the satisfaction. Customer loyalty is positively and significantly influenced by customer satisfaction. Based on the contribution of indicator constructs, to achieve customer loyalty as the Telkomsel GSM prepaid card providers need to maintain and improve Sympathy area range, sound quality, connection and signal quality. With the improvement of the quality of the customer will feel the positive perceived value that includes the sacrifice of energy, effort, and time the customer. Additionally, it will create customer satisfaction that keeps the sympathy GSM prepaid card service as well as providing recommendations and positive word of mouth to others.